EVALUATION OF SHIGRU (MORINGA OLEIFERA LAM) SEED IN SANGYAHARAN IN POST OPERATIVE PAIN MANAGEMENT - Medhi, *Champak; Das, Bhabesh (International Journal of Ayurveda and Pharma Research, 2017)
There are a number of analgesics for post operative pain management. But all the analgesics available have side effects and no analgesic can give complete analgesia in the post operative pain management. Therefore to search an indigenous drug for post operative pain management this research work was selected.Aim: The main object of this work was to search an indigenous drug for post operative pain management.Materials & Methods: For this study sixty patients of fistula in ano of either sex were selected of ASA grade I & II. Patients of group I were considered as control group & group II were considered as trial group. The patients of group I (control group) were given diclofenac sodium (50mg) at 10 PM of preoperative night and 1 hour before operation orally with an ounce of plain water and primary threading was done under spinal anasesthesia. The patients of group II (trial group) were given one capsule of Shigru seed Ghansatva (500 mg) at 10pm of preoperative night and 1 hour before operation orally with an ounce of plain water and primary threading was done under spinal anaesthesia. The patients of group I were given diclofenac sodium 50mg orally and the patients of group II were given Shigru seed Ghansatva capsule (500 mg) orally when the patients felt pain in the post operative period.Result: Shigru seed Ghansatva in post operative pain management showed its Vedanasthapana properties.Conclusion: Shigru seed in the form of Ghansatva has Vedanahar (analgesic) and Sothahar (anti-inflammatory) properties like tablet diclofenac sodium used as premedicants.